2013
DOI: 10.1007/s00221-013-3469-5
|View full text |Cite
|
Sign up to set email alerts
|

Anticipatory synergy adjustments: preparing a quick action in an unknown direction

Abstract: We studied a mechanism of feed-forward control of a multi-finger action, namely anticipatory synergy adjustments (ASAs) prior to a quick force correction in response to a change in the gain of the visual feedback. Synergies were defined as co-varied across trials adjustments of commands to fingers that stabilized (decreased variance of) the total force. We hypothesized that ASAs would be highly sensitive to prior information about the timing of the action but not to information on its direction, i.e., on wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
(46 reference statements)
1
15
0
Order By: Relevance
“…Other variables showed no clearly identifiable ASAs, possibly because the actions were not associated with fast enough changes in those variables. Note that the assumed function of ASA is to phase out synergies stabilizing a variable in preparation to its quick change (Zhou et al 2013); ASAs may not be needed if the variable does not change quickly.…”
Section: Discussionmentioning
confidence: 99%
“…Other variables showed no clearly identifiable ASAs, possibly because the actions were not associated with fast enough changes in those variables. Note that the assumed function of ASA is to phase out synergies stabilizing a variable in preparation to its quick change (Zhou et al 2013); ASAs may not be needed if the variable does not change quickly.…”
Section: Discussionmentioning
confidence: 99%
“…Such synergic adjustments have been reported in force production tasks by a redundant set of effectors including bilateral tasks (19, 20). A recent study has shown that these adjustments are organized in a subtle way reflected in different patterns of force co-variation when the visual feedback was computed using varying gains for the force of one of the effectors (21). …”
Section: Discussionmentioning
confidence: 99%
“…Depending on the context, high stability of biological movement may be beneficial (for example, during steady-state tasks) or detrimental (for example, during very fast actions). Recently, an ability of the central nervous system to adjust stability properties of an ongoing action has been discovered: Several studies have shown that humans have an ability to adjust their synergies in preparation for a quick action (Olafsdottir et al, 2005; Shim et al, 2005; Zhou et al, 2013). Such anticipatory synergy adjustments (ASAs) are seen as a drop in the synergy index (relative amount of V UCM in the total variance) 200–300 ms prior to the initiation of a quick action.…”
Section: The Application Of the Concept Of Motor Synergies To Quanmentioning
confidence: 99%